Development and validation of a health educational booklet: A parent's role in water safety and drowning prevention - Noor Hamzani Farizan; Rosnah Sutan; Rozita Hod; Kulanthayan KC Mani (College of Public Health Sciences, Chulalongkorn University, 2020)
Purpose - This study aimed to develop and validate a health education booklet (Be SAFE booklet) as a guide to improving knowledge, attitude, and practice toward drowning prevention and water safety among parents of primary school children in a local community in Selangor. Design/methodology/approach - This methodological study was conducted in two phases: the development of the content, and validation of the educational material. Booklet development involved content survey and design development. These steps consisted of a content analysis method, information from current literature, document analysis from the stakeholder, and input from parents or guardians and children. The validation by nine panel experts and 15 parents/guardians involved both review, content validity, and face validity. Findings - The booklet was developed by emphasizing on four main aspects related to drowning prevention and water safety; namely, supervision, alertness, first aid, and education. The assessment rated by the content validity index (CVI), resulted in an I-CVI ranging from 0.78 to 1 and S-CVI of 0.94; the face validity achieved a level of agreement with an average of 94 percent. The results indicated that the Be SAFE booklet was validated and could be considered useful in helping to promote drowning prevention and water safety among primary school pupils' parents. Originality/value - This article contributed ideas for the concept and aspect of health messages to be incorporated into health education materials for drowning prevention and water safety.